Transdermal drug targeting and functional imaging of tumor blood vessels in the mouse auricle - Schröder, Hannes; Komljenovic, Dorde; Hecker, Markus; Korff, Thomas (The FASEB journal, 2016)
Subcutaneously growing tumors are widely utilized to study tumor angiogenesis and the efficacy of antiangiogenic therapies in mice. To additionally assess functional and morphologic alterations of the vasculature in the periphery of a growing tumor, we exploited the easily accessible and hierarchically organized vasculature of the mouse auricle.
First published: 06 November 2015
Gesehen am 22.05.2020